2020
DOI: 10.21237/c7clio11142348
|View full text |Cite
|
Sign up to set email alerts
|

The Causes and Mechanisms of the Ukrainian Crisis of 2014: A Structural–Demographic Approach

Abstract: This article tests the hypothesis that Ukraine experienced a state breakdown in 2014. The methodology employed to test this statement is based on achievements of structural-demographic theory, created by Jack Goldstone and developed by Peter Turchin. The reasons for a fiscal crisis, intra-elite conflict and mass mobilization (the three criteria for a state breakdown) are discussed. It is demonstrated that budget management in Ukraine was ineffective, and, coupled with an unbalanced political system, led to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The goal of Cliodynamics remains the same, however: developing and drawing on the rich data of economic, political, social, archeological, cultural and demographic history to identify persistent patterns and relationships in the history of human societies, and to develop and test theories of social change (Turchin 2010;. One of the virtues of Cliodynamics as journal is that it welcomes contributions from a vast range of academic disciplines -we have published research from archeology, ecology, sociology, comparative history, and even such novel fields as econophysics, big history, and political demography (Spier 2011;Morris 2012;Thompson and Sakuwa 2013;Malkov 2014;Currie et al 2015;Zinkina et al 2016;Goldstone 2017;Feinman 2018;Roman and Palmer, 2019;Shevsky 2020;Hooper 2021). We will continue to seek and publish articles that deal with the full range of historical dynamics -patterns of change, long-term trends, critical events such as divergences and turning points, and typologies and analyses of sequences of historical events.…”
Section: New Leadershipmentioning
confidence: 99%
“…The goal of Cliodynamics remains the same, however: developing and drawing on the rich data of economic, political, social, archeological, cultural and demographic history to identify persistent patterns and relationships in the history of human societies, and to develop and test theories of social change (Turchin 2010;. One of the virtues of Cliodynamics as journal is that it welcomes contributions from a vast range of academic disciplines -we have published research from archeology, ecology, sociology, comparative history, and even such novel fields as econophysics, big history, and political demography (Spier 2011;Morris 2012;Thompson and Sakuwa 2013;Malkov 2014;Currie et al 2015;Zinkina et al 2016;Goldstone 2017;Feinman 2018;Roman and Palmer, 2019;Shevsky 2020;Hooper 2021). We will continue to seek and publish articles that deal with the full range of historical dynamics -patterns of change, long-term trends, critical events such as divergences and turning points, and typologies and analyses of sequences of historical events.…”
Section: New Leadershipmentioning
confidence: 99%
“…The examples of an 'unexpected' sharp increase in the fortune of those close to the president confirm this interpretation. However, the emerging of Yanukovych's 'Family' clan failed to re-subordinate the media, which became the main mechanism for mass mobilization (for more details, see Shevsky 2020).…”
Section: Case Analysismentioning
confidence: 99%
“…Turchin (2020) quantified the impact of demographics on political instability in the United States and western Europe, then predicted that social instability is on the rise, for all of these countries [19] . Shevsky (2020) confirmed the collapse of Ukraine in 2014 through the three criteria, which can be extended by the demographic structure theory, and he had explored the objective reasons for this collapse process [20] . Bennett (2016) used a spatially resolved agent-based modeling of agrarian empires, and found that this theory can explain the spread of large-scale agriculture, throughout the Old World since the Bronze Age [25] .…”
Section: Introductionmentioning
confidence: 98%
“…Greatly seizing both macro and micro-level mechanisms, the demographic structural theory is explanatory to clarify the sociological mechanisms of empires [5] . It is initially proposed by Goldstone (1991) and developed by Turchin (2003) [20] . The main viewpoint is that population growth and the productivity of land (gains) have joint effects on social institutions, such as persistent price inflations, increasing uprisings, wage protests, the lack of jobs, and ideological conflicts [14] in the society.…”
Section: Introductionmentioning
confidence: 99%